Monetary Policy Is Not Always Systematic and Data-Driven : Evidence from the Yield Curve - Bulir, Ales (IMF Working Papers; Working Paper ;, 2020)
Does monetary policy react systematically to macroeconomic innovations? In a sample of 16 countries - operating under various monetary regimes - we find that monetary policy decisions, as expressed in yield curve movements, do react to macroeconomic innovations and these reactions reflect the monetary policy regime. While we find evidence of the primacy of the price stability objective in the inflation targeting countries, links to inflation and the output gap are generally weaker and less systematic in money-targeting and multiple-objective countries.